Emo Demo Pencegahan Gizi Kurang pada Balita dengan Pemanfaatan Pangan Lokal di Kecamatan Kaliwungu Selatan - Ardian Candra Mustikaningrum; Sulastri; Atala Rania Insyira (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2026)
The problem of malnutrition in toddlers remains a public helath challenge that requires educational interventions based on behavioral change. The low nutritional knowledge of mothers regarding toddler feeding and the less than optimal utilization of local foods are factors that affect children’s nutritional status. The Emotional Demonstration (Emo Demo) activity is an educational method based on behavioral change that uses an emotional approach and interactive demonstrations to improve the understanding of toddler mothers. This community service activity aims to improve the knowledge and practice of toddler mothers regarding the prevention of malnutrition through the Emo Demo method by utilizing local foods in Kaliwungu District. The implementation method uses participatory education through demonstrations, educational games, toddler finger food simulations, and local food processing practices such as dragon’s feet. The activity participants were 40 toddler mothers and helath cadres. Evalutions was carried out using a pretest and posttest of knowledge. Data analysis used a paired t-test. The results showed an average knowledge score increased from 60,85 ± 9,74 to 83,10 ± 7,92 with a p value  0,001 (p= <0,05). Furthhermore, the practice of utilizing local food increased from 52,5% to 80 %. The Emo Demo activity proved effective in increasing mother’s understanding of toddler’s malnutrition prevetion and the use of local food as a nutritious food source for toddlers.     ABSTRAK Masalah kurang gizi pada Balita masih menjadi tantangan kesehatan masyarakat yang memerlukan intervensi edukasi berbasis perubahan perilaku. Rendahnya pengetahuan gizi ibu mengenai pemberian makan Balita dan kurang optimalnya pemanfaatan pangan lokal menjadi faktor yang mempengaruhi status gizi anak. Kegiatan Emotional Demonstration (Emo Demo) merupakan  metode edukasi berbasis perubahan perilaku yang menggunakan pendekatan emosional dan demonstrasi interaktif untuk meningkatkan pemahaman ibu Balita. Kegiatan pengabdian masyarakat ini bertujuan meningkatkan pengetahuan dan praktik ibu Balita mengenai pencegahan gizi kurang melalui metode Emo Demo dengan pemanfaatan pangan lokal di Kecamatan Kaliwungu. Metode pelaksanaan menggunakan edukasi partisipatif melalui demonstrasi, permainan edukatif, simulasi finger food balita, dan praktek pengolahan pangan lokal berupa kaki naga. Peserta kegiatan sebanyak 40 ibu balita dan kader kesehatan. Evaluasi dilakukan menggunakan pretest dan posttest pengetahuan. Analisis data menggunakan uji paired t-test. Hasil menunjukkan rata-rata skor pengetahuan meningkat dari 60,85 ± 9,74 menjadi 83,10 ± 7,92 dengan nilai p= 0,001 (p= <0,05).  Selain itu, praktik pemanfaatan pangan lokal meningkat dari 52,5% menjadi 80%. Kegiatan Emo Demo terbukti efektif meningkatkan pemahaman ibu Balita mengenai pencegahan gizi kurang dan pemanfaatan pangan lokal sebagai sumber makanan bergizi bagi Balita.